Development of competitive strategies of a cleaning company and analysis of the cleaning services market ("Journal "U". Economy. Management. Finance.", 2025)
The article discusses the development of competitive strategies for the cleaning company "ClearVision" based on a comprehensive market analysis. The study covers Porter's classic strategies (cost leadership, differentiation, focus) and Kotler's modern approaches. A detailed SWOT analysis was carried out, and the company's key competitive advantages were identified: the use of environmentally friendly products, a wide range of services, and optimal pricing. Special attention is paid to calculating competitiveness using mathematical methods and analyzing the target audience. As a result, the choice of a differentiation strategy was justified, practical recommendations were developed for the promotion of services and the assessment of the economic effectiveness of the project.
Keywords: strategy; coefficient; costs; cleaning services; market analysis; budget